Soviet Nationalities Problems. (U.S. Congressional Research., 1989)
Considers the challenges posed by the recent upsurge of unrest among many of the non-Russian nationalities in the Soviet Union, and assesses the political danger which the unrest constitutes for Gorbachev and his reform programs. Discusses the implications for U.S.-Soviet relations and U.S. concerns for human rights.